Validity and specificity of BOLD effects and their correction in 1H-fMRS - Just, Nathalie (Frontiers in Neuroscience, 2024)
PurposeThis study aimed to characterize blood oxygen level-dependent (BOLD) effects in proton magnetic resonance (1H-MR) spectra obtained during optogenetic activation of the rat forelimb cortex to correct and estimate the accurate changes in metabolite concentration.MethodsFor a more comprehensive understanding of BOLD effects detected with functional magnetic resonance spectroscopy (fMRS) and to optimize the correction method, a 1 Hz line-narrowing effect was simulated. Then, proton functional magnetic resonance spectroscopy (1H-fMRS) data acquired using stimulated echo acquisition mode (STEAM) at 9.4T in rats (n = 8) upon optogenetic stimulation of the primary somatosensory cortex were utilized. The data were analyzed using MATLAB routines and LCModel. Uncorrected and corrected 1H-MR spectra from the simulated and in vivo data were quantified and compared. BOLD-corrected difference spectra were also calculated and analyzed. Additionally, the effects of stimulated and non-stimulated water on the quantification of metabolite concentration swere investigated.ResultsSignificant mean increases in water and N-acetylaspartate (NAA) peak heights (+1.1% and +4.5%, respectively) were found to be accompanied by decreased linewidths (−0.5 Hz and −2.8%) upon optogenetic stimulation. These estimates were used for further defining an accurate line-broadening (lb) factor. The usage of a non-data-driven lb introduced false-positive errors in the metabolite concentration change estimates, thereby altering the specificity of the findings. The water and metabolite BOLD contributions were separated using different water scalings within LCModel.ConclusionThe linewidth-matching procedure using a precise lb factor remains the most effective approach for accurately quantifying small (±0.3 μmol/g) metabolic changes in 1H-fMRS studies. A simple and preliminary compartmentation of BOLD effects was proposed, but it will require validation.